IMPROVEMENT OF CORPORATE PLANNING PROCESS IN CURRENT CONDITIONS - PANASENKO, LARISA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The theoretical views of Ukrainian scholars on corporate planning and one of the key concepts – the planning process – are considered in the article. The necessity of planning for the enterprise in modern crisis conditions is substantiated. Despite the large number of publications on corporate planning, the concept of "planning process" is not fully defined by Ukrainian scholars. It does not have a clear structure and lacks clear sequence of stages. Interpretation of the concept of corporate planning is not adapted to modern crisis conditions. When applying the "planning process" the potential of economic and mathematical methods and possible automation is not realized.Views on the planning process and their shortcomings are highlighted, and on their basis, the definition of the corporate planning process is formed. The definition of the corporate planning process is adjusted taking into account the functional approach to enterprise management. The stages of the enterprise planning process are highlighted. It is proposed to apply economic and mathematical methods at the last stage, namely linear regression. It is recommended to select the factors that affect the planning of enterprise profits and accordingly calculate the value of their regression. Thus, the factors whose parameters have the greatest value of regression can be used in the implementation of planned tasks of the enterprise to ensure the company's profit.Selection of factors and calculation of the value of their regression can significantly improve the planning process and allow design an algorithm for specialized software.
Keywords: enterprise management; corporate planning; planning process; stages of the planning process; economic and mathematical methods; linear regression; functional approach; cybernetic approach